Diagnosis of single umbilical artery and risk of foetal congenital malformations by prenatal ultrasound: a retrospective study - Junjin Yu; Qingqin Wu; Fanbin Kong; Yan Ning (BMC Pregnancy and Childbirth, 2024)
Abstract Background Single umbilical artery (SUA) is strongly associated with foetal structural abnormalities; however, the exact pattern of this association has not been described. We aimed to investigate the occurrence of malformations in singleton pregnancies with SUA in China and to study the association between the absent side of the umbilical artery and foetal malformations. Methods This was a retrospective study of singleton pregnancies for which routine first-trimester anatomical screening was performed at 11+ 0-13+ 6 gestational weeks and, if the pregnancy continued, a second-trimester scan was performed at 20+ 0-24+ 0 weeks. Data were extracted from records at the referral centre, the Obstetrics and Gynecology Hospital of Fudan University, between January 2011 and April 2019 (n = 47,894). Using logistic regression, the odds ratios (OR) with 95% confidence intervals (CIs) were calculated for malformations associated with SUA. Results The incidence of SUA in our study was 2.0% (970/47,894). Of all foetuses with SUA, 387 (39.9%) had structural malformations. The malformation type varied, with cardiovascular complications being the most common. A robust association was observed between SUA and oesophageal stenosis or atresia (OR: 25.33), followed by cardiovascular (OR: 9.98–24.02), scoliosis (OR: 18.62), genitourinary (OR: 2.45–15.66), and brain malformations (OR: 4.73–9.12). The absence of the left umbilical artery (n = 445, 45.9%) was consistent with that of the right umbilical artery (n = 431, 44.4%). Furthermore, a significantly higher rate of an absent right than the left umbilical artery (p<0.01) was observed in SUA with foetal abnormalities than in SUA with no malformations. Conclusions Overall, we observed a higher risk of various specific malformations in foetuses with SUA, and a strong association between SUA and oesophageal stenosis or atresia. The absence of the right umbilical artery was most common in foetuses with SUA and structural malformations. This study provides a reference for ultrasonographers in conducting foetal structural screening for pregnant women with SUA.